Conceptions and practices of nurses in palliative patient care and family (Research, Society and Development, 2022)
Objective: to describe the conceptions and practices of nurses in the care of palliative patients and their families. Methodology: qualitative, exploratory and descriptive research, developed with twelve nurses working in the inpatient units, where palliative care is provided. Data collection took place through a semi-structured interview, recorded and later fully transcribed. For data analysis, thematic content analysis proposed by Minayo was used. Ethical principles in health were respected, according to the Resolution of the National Health Council No. 466/2012. The research project was approved by the Research Ethics Committee of the Universidade do Oeste de Santa Catarina, under Opinion number 1,968,812. Results: from the analysis, two thematic categories emerged, and, in this article, the thematic category will be presented - Conceptions and practices of nurses in the care of palliative patients and families, where it is observed that, in addition to measures of comfort and pain relief , nurses assign great importance in caring for the emotional and psychological dimension of the patient and family, which are essential for coping with the terminality process. Final considerations: it is essential for nurses who provide palliative care to pay attention to the humanistic practices that involve this type of care, such as knowing how to listen, offering support and support, respecting decisions, being present and having empathy with the patient and family. With this, the patient-family-nurse triad is strengthened and finds the best way to face the process of death and dying. This is configured in the principle of humanization of care, indispensable in palliative care.